Negara maslahah : pemikiran al-Ghazali dan konteks politik Malaysia - Alies Anor Abdul , 1955- (Firdaus Press Sdn. Bhd, 2016)
On thought and thinking Islamic political theory of al-Ghazali and Malaysia political aspects